Penuntun Praktikum Elektronik Berbasis Green Chemistry dengan Model Pembelajaran Learning Cycle-7e pada Materi Asam-Basa - Hafizatul Ilma; Leni Marlina; Ravensky Yurianty Pratiwi (Chemistry Education Department of Education and Teaching Faculty, 2022)
The Covid-19 virus in Indonesia has caused face-to-face learning switching to online learning. In the 2013 curriculum there is skill competency, so that in learning chemistry to achieve that, practicum activities are carried out at home and environmentally friendly. This research is an R & D (Research and Development) aimed to knowing the level of validity and knowing response of students to an electronic practicum guide based on green chemistry with the learning cycle-7e learning model on acid-base material. The development and research procedure uses the ADDIE model, due to the limited time the stages carried out are ADD (Analysis, Design, and Developme). The study involved four validators, namely one media expert validator, one language validator, and two material expert validators. The trials carried out are one to one and small group. The subjects were students of SMA Muhammadiyah 1 Palembang. Data collection instruments used validation sheets and student response questionnaires. Data analysis used qualitative and quantitative analysis. The results of this study indicate that the green chemistry-based electronic practicum guide with the learning cycle-7e learning model on acid-base material is very valid based on the validation results of material, media, and language experts with an average percentage obtained of 83.5%. The students' responses were categorized as very good, where in the one-to-one trial percentage is 98.6% in the very good category, in the small group trial the percentage is 95.2% in the very good category.